Development of Control Method for the Radar Antenna Motion to Enhance Sectorial Detection (Damascus University Journal for engineering sciences, 2021)
Many ethology to develop radar system propagated hugely for all subsystems of radar. One of the most important subsystem of radar is detection system, which is developed by many methods because it suffers problem of air impedance and big size antenna during sector detection process. Direct Torque Control by radar antenna motor is one of the most important used method to achieve sector scanning in electronic scanning systems. This paper presents process of canning sector for radar antenna using direct torque control developed by artificial neural network, where it could estimate flux precisely more than classic DTC. This ANN- DTC filters tolerances of stator resistance because of changes in load of antenna motor, which is caused big size of antenna and air windy resistance, all of that reproduces electromagnetic torque with least of dynamic and static error than when classic DTC is used. So streamline of motion antenna is done.  DTC and ANN – DTC are expressed. Motor of radar antenna to achieve sector scanning is modeled using MatLab program for both of DTC and ANN – DTC. Speed and torque responses of DTC and ANN – DTC and error signals are founded. Comparing between of DTC and ANN – DTC is achieved depended on mean square error MSE. The results improves superiority of ANN – DTC on DTC to achieve sector scanning process though big size antenna and windy air resistance. In addition many cases for change of torque's motion of antenna are studied according to many sizes of radar antenna, and torque carves are founded out. Carve of maximum torque change with size of antenna is obtained. Proposal ANN – DTC confirms it superiority on classic ANN for feeding motion radar antenna to achieve sector scanning for different sizes of antenna.
Keywords: Radar; Sectorial Detection; ANN